2022
DOI: 10.1002/alz.068822
|View full text |Cite
|
Sign up to set email alerts
|

Single domain antibody‐based non‐invasive in vivo imaging of tau pathology

Abstract: BackgroundNumerous studies have shown that the extent of pathological tau protein in the brain correlates strongly with the severity of Alzheimer’s dementia at the time of death, and similar association with functional phenotypes have been seen in other tauopathies. In recent years, several dye‐based imaging probes with selectivity for tau aggregates have been developed. However, all are β‐sheet binders with varying affinity for different amyloids, and thereby lack specificity for tau lesions. In contrast, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…In the next phase of our study, we assessed the in vivo effectiveness of the unmodified and modified sdAb in an M83 mouse model of synucleinopathy. Previous findings from our diagnostic imaging study indicated that the anti-α-syn sdAbs 2D8 and 2D10 traversed the blood-brain barrier and colocalized with intraneuronal α-syn aggregates after an intravenous injection in this mouse model ( 37 ). The intensity of the sdAb brain signal correlated strongly with the levels of pathological α-syn in the brain, with 2D10 showing a clear superiority over 2D8 in signal intensity, and a slight advantage in degree of correlation and specificity for α-syn lesions.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…In the next phase of our study, we assessed the in vivo effectiveness of the unmodified and modified sdAb in an M83 mouse model of synucleinopathy. Previous findings from our diagnostic imaging study indicated that the anti-α-syn sdAbs 2D8 and 2D10 traversed the blood-brain barrier and colocalized with intraneuronal α-syn aggregates after an intravenous injection in this mouse model ( 37 ). The intensity of the sdAb brain signal correlated strongly with the levels of pathological α-syn in the brain, with 2D10 showing a clear superiority over 2D8 in signal intensity, and a slight advantage in degree of correlation and specificity for α-syn lesions.…”
Section: Resultssupporting
confidence: 51%
“…Therefore, the half-life of sdAbs in blood is relatively short, typically less than 2 h, rendering them potentially less suitable as therapeutic candidates compared to whole antibodies that usually have blood half-life of 1-3 weeks ( 68 ). However, during our imaging study, we observed that at the time point of 24 and 96 hours following a single intravenous injection of near-infrared-labeled 2D8, its brain signal registered at 47% and 22% of peak signal, respectively ( Supplemental Figure 7 , ( 37 )). This relatively slow brain clearance is likely explained by sdAb binding to α-syn aggregates within neurons.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…They are also highly amenable to engineering to increase their half-life and enhance their degradation capabilities. We have described in detail the development of our anti-tau sdAbs by immunizing a llama with recombinant tau and pathological tau derived from a human tauopathy brain (21,22). We have also reported on the e cacy of two of them in tauopathy culture models and by in vivo microdialysis in a mouse tauopathy model, as well as the suitability of one of them as a diagnostic imaging agent in two different tauopathy mouse models (21,22).…”
Section: Introductionmentioning
confidence: 99%